(untitled) (Research, Society and Development, 2021)
The objective was to describe the feedback syndrome with a focus on risk factors and diagnoses. Metabolic complications resulting from refeeding after prolonged fasting can lead to clinical pathology currently defined as refeeding syndrome. Initially described during World War II, when prisoners of war experienced heart failure after nutritional replacement, the feedback syndrome is a severe, potentially fatal, electrolyte disorder that occurs after the reintroduction of the diet, whether orally, enterally, or parenterally. Multiple systems can be affected, including cardiovascular, respiratory, and hematologic, skeletal and neurological muscle.